Dosimetric comparison of high dose rate brachytherapy and intensity-modulated radiation therapy for cervical carcinoma - Shwetha, B. (Medknow Publications, 2011)
Intracavitary brachytherapy is an integral part of radiotherapy for locally advanced gynecologic malignancies. A dosimetric intercomparison of high dose rate intracavitary brachytherapy (HDR_BT) and intensity-modulated radiotherapy in cervical carcinoma has been made in the present study. CT scan images of 10 patients treated with HDR_BT were used for this study. A sliding-window IMRT (IMRT_SW) and step-and-shoot IMRT plans were generated using 6-MV X-rays. The cumulative dose volume histograms of target, bladder, rectum and normal tissue were analyzed for both techniques and dose distributions were compared. It was seen that the pear-shaped dose distribution characteristic of intracavitary brachytherapy with sharp dose fall-off outside the target could be achieved with IMRT. The integral dose to planning target volume was significantly higher with HDR_BT in comparison with IMRT. Significant differences between the two techniques were seen for doses to 1 cc and 2 cc of rectum, while the differences in 1 cc and 2 cc doses to bladder were not significant. The integral doses to the nontarget critical and normal structures were smaller with HDR_BT and with IMRT. It is concluded that IMRT can be the choice of treatment in case of non-availability of HDR brachytherapy facilities or when noninvasive treatments are preferred